12α-Hydroxylated bile acid enhances accumulation of adiponectin and immunoglobulin A in the rat ileum - Reika Yoshitsugu; Hongxia Liu; Yoshie Kamo; Akari Takeuchi; Ga-Hyun Joe; Koji Tada; Keidai Kikuchi; Nobuyuki Fujii; Shinri Kitta; Shota Hori; Manami Takatsuki; Hitoshi Iwaya; et al. (Scientific Reports, 2021)
Abstract We previously reported that dietary supplementation with cholic acid (CA), the primary 12α-hydroxylated (12αOH) bile acid (BA), reduces plasma adiponectin concentration in rats. The aim of this study was to examine the distribution of adiponectin in the body of CA-fed rats and its influence on mucosal immunoglobulin A concentration in the intestine. Rats were fed a diet supplemented with or without CA (0.5 g CA/kg diet) for 13 weeks. A reduction in plasma adiponectin level was observed from week 3. At the end of the experiment, the CA diet reduced plasma adiponectin concentration both in the portal and aortic plasma. Accumulation of adiponectin was accompanied by an increase in cadherin-13 mRNA expression in the ileal mucosa of CA-fed rats. No increase was observed in adiponectin mRNA expression in the ileal and adipose tissues of the CA-fed rats. Immunoglobulin A concentration in the ileal mucosa was elevated in the CA-fed rats and was correlated with the ileal adiponectin concentration. 12αOH BAs may modulate mucosal immune response that are involved in the accumulation of adiponectin in the ileum.